Red-Shifted Firefly Luciferase Optimized for Candida albicans In vivo Bioluminescence Imaging - Dorsaz, Stephane; Coste, Alix T.; Sanglard, Dominique (Frontiers in Microbiology, 2017)
Candida albicans is a major fungal pathogen causing life-threatening diseases in immuno-compromised patients. The efficacy of current drugs to combat C. albicans infections is limited, as these infections have a 40-60% mortality rate. There is a real need for novel therapeutic approaches, but such advances require a detailed knowledge of C. albicans and its in vivo pathogenesis. Additionally, any novel antifungal drugs against C. albicans infections will need to be tested for their in vivo efficacy over time. Fungal pathogenesis and drug-mediated resolution studies can both be evaluated using non-invasive in vivo imaging technologies. In the work presented here, we used a codon-optimized firefly luciferase reporter system for detecting C. albicans in mice. We adapted the firefly luciferase in order to improve its maximum emission intensity in the red light range (600-700 nm) as well as to improve its thermostability in mice. All non-invasive in vivo imaging of experimental animals was performed with a multimodal imaging system able to detect luminescent reporters and capture both reflectance and X-ray images. The modified firefly luciferase expressed in C. albicans (Mut2) was found to significantly increase the sensitivity of bioluminescence imaging (BLI) in systemic infections as compared to unmodified luciferase (Mut0). The same modified bioluminescence reporter system was used in an oropharyngeal candidiasis model. In both animal models, fungal loads could be correlated to the intensity of emitted light. Antifungal treatment efficacies were also evaluated on the basis of BLI signal intensity. In conclusion, BLI with a red-shifted firefly luciferase was found to be a powerful tool for testing the fate of C. albicans in various mice infection models.